P47 De-novo antiviral therapy with nucleos(t)ide analogues in 'real-life' patients with chronic hepatitis B infection: comparison of virological responses between lamivudine + adefovir vs entecavir vs tenofovir therapy. (6th September 2011) - Carey, I; Nguyen DorothyJoe, H; Al-Freah, M; Knighton, S; Bruce, M; Suddle, A; Harrison, P M; Agarwal, K
Abstract : Introduction: Several nucleos(t)ide analogues (NA) are approved for the treatment of chronic hepatitis B (CH-B); all aim to control HBV replication with minimal risk of drug-resistance and toxicity. Limited comparative data exist assessing differences between viral responses to different de-novo therapeutic regimens in real-life cohorts. Aim: To assess and compare virological and serological responses in 3 real-life CH-B de-novo therapeutic cohorts—lamivudine 100 mg/d + adefovir 10 mg/d (LAM+ADV) combination therapy vs entecavir 0.5 mg/d (ETV) vs tenofovir 245 mg/d (TDF) monotherapies. Method: Patients: NA therapy naive 406 CH-B patients treated at a single-centre practice [median 30 months (m), range 3–72] were split into three groups according therapy regimen: LAM+ADV (n=192, 78% males, median age 40 y, 35% HBeAg+, 34% cirrhosis, median duration 36 months), ETV (n=154, 79% males, median age 42 y, 31% HBeAg+, 34% cirrhosis, median duration 28 months) and TDF (n=60, 50% males, median age 40 y, 23%HBeAg+, 25% cirrhosis, median duration 9 months). HBV DNA viral load tested by real-time PCR [log10 IU/ml], serology for HBeAg/HBsAg were compared between baseline, months 3, 6, 9 and 12. Five responses, evaluated by change in serum HBV DNA, were recorded: (1) complete (CR) <12 IU/ml; (2) partial (PR), fall >3log10 but >12 IU/ml; (3) slow (SR), fall 2–3 log10; (4) non-response (NR), fall <1 log10; 5) viral breakthrough (VB), rise >1 log10 from nadir. HBV genotypic resistance was tested pre-treatment and at the time of SR, NR or VB by direct sequencing. Results: Baseline HBV DNA was similar in all cohorts (median log10 4.6 vs 4.4 vs 4.2 IU/ml), higher proportions achieved CR in TDF cohort than LAM+ADV and ETV (m3: 78%vs 48% and 53%, p<0.01; m6: 82% vs 60% and 65%, p=0.02; m9: 86% vs 62% and 55%, p<0.01), but were similar at m12: 80% vs 73% and 76% and there were no differences in PR, SR and NR in all groups. HBV DNA decreased in analogous rate in all groups. 2 patients in LAM+ADV and ETV groups developed VB. No viral mutations associated with drug resistance were detected in the LAM + ADV and TDFgroup, including those with VB, NR or SR; in contrast 1 ETV patient with SR at m12 (genotype C) developed mutation rtM204I. HBeAg seroconversion was more frequent in LAM + ADV cohort vs ETV and TDF (21% vs 8% and 7%, p=0.06) and HBsAg seroconversion occurred only in LAM + ADV and ETV patients (2% and 1%). Conclusion: De-novo antiviral therapy with different therapeutic approaches of nucleos(t)ide analogues LAM+ADV, ETV and TDF achieves similar efficacy within 12 months of treatment in real-life patient cohorts with CH-B.